FAKTOR RISIKO ERGONOMI DENGAN TERJADINYA KELUHAN MUSCULOSKELETAL DISORDERS PADA PEKERJA OVERHAUL - Iin Viradiani (The Indonesian Journal of Occupational Safety and Health, 2018)
PT PJB UPHT is a company that runs a service in maintaining a unit of power station. The job description includes overhaul that is done manually by its workers. This work that is done manually has a risk of suffering musculoskeletal. The aim of this study is to examine the relation between the risk of ergonomic’s factor with musculoskeletal disorders on overhaul workers in mechanical turbine department. This study is an observational descriptive research. The tool used to measure musculoskeletal disorders was Nordic Body Map (NBM) checklist sheet. In order to measure the work postures of workers, REBA (Rapid Entire Body Assessment) method was employed. Meanwhile, questionnaires were used to know types of work. The total population of this research was 17 workers in mechanical turbine. The data was analyzed using cross tabulation to see the relation strength. The result of this study shows that all overhaul workers in mechanical turbine suffer from musculoskeletal. It can be concluded that the risk of ergonomic’s factor in this case is type of work have strong relation to the suffering of musculoskeletal on workers.Keywords: mechanical turbine workers, musculoskeletal disorders, the risk of ergonomic’s factor